Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.5162
|View full text |Cite
|
Sign up to set email alerts
|

FRI0141 Vaccination decisions and incidence of neonatal infections in mothers exposed to biologicals during pregnancy

Abstract: BackgroundRheumatologic diseases commonly affect women of childbearing age(.1, 2 There is currently limited data available regarding the safety of vaccinations in infants after in utero exposure to biologics.ObjectivesTo determine the vaccination decisions of mothers with rheumatologic diseases exposed to biologics during pregnancy and the incidence of serious neonatal infections after third trimester exposure.MethodsAll Australian women with inflammatory arthritis, exposed to biologics during the preconceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…In some of the included publications the type of biologic used was not specified for the outcomes. In general, these studies did not show any abnormal outcomes in children exposed to biologics during pregnancy/lactation [155][156][157][158][159][160][161][162][163][164][165][166][167].…”
Section: Biologics (In General Not Specified)mentioning
confidence: 99%
“…In some of the included publications the type of biologic used was not specified for the outcomes. In general, these studies did not show any abnormal outcomes in children exposed to biologics during pregnancy/lactation [155][156][157][158][159][160][161][162][163][164][165][166][167].…”
Section: Biologics (In General Not Specified)mentioning
confidence: 99%
“…Cohort studies and case series have described safe vaccination without serious complications in infants who received rotavirus vaccine after in utero exposure to mAbs, 55 including those who were exposed during the third trimester. 56 A systematic review of live vaccine outcomes before 12 months for 276 in utero exposures found that administration of the MMR and rotavirus vaccines were not associated with harmful adverse reactions; however, the BCG vaccine was and should be cautioned against due to increased risk of fatal disseminated BCG infection after vaccination. 57 Current guidelines recommend that all infants exposed to mAbs in utero receive inactivated immunizations according to routine schedule.…”
Section: Immunizationmentioning
confidence: 99%
“…Case series 65,82 and more recently, cohort studies 59,76,96 have described exposed infants who received this vaccine without serious complications, such as vaccine-associated rotavirus disease. 83,[97][98][99] Rotavirus infection from the live-attenuated vaccine has been limited primarily to patients with severe combined immune deficiency, [100][101][102] suggesting that this adverse event is mostly observed in children with severe T-and B-cell immunodeficiency and not with other immune defects or mild immunosuppression. [103][104][105] Specialist assessment of immune function is recommended before considering administration of rotavirus vaccination, with careful review of the specific drug exposure.…”
Section: Should Infants Exposed To Biologics Be Immunized?mentioning
confidence: 99%